Teacher Evaluations and Contextualized Self- Efficacy: Classroom Management, Instructional Strategies and Student Engagement (Journal of School Administration Research and Development, 2019)
Teacher feedback from administrators can play an important role in continuous teacher development, especially in making the classroom safe, challenging, and engaging for all students. In this study, interview data was collected from 28 high school teachers from three different comprehensive high schools within the same school district in Southern California to examine teachers' perceptions of feedback from administrators in the areas of classroom management, instructional feedback, and student engagement. Results indicated that teacher feedback from administrators can play an important role in increasing teachers' self-efficacy. Types of feedback varied depending on the context (classroom management, instructional strategies, and engaging students), individual teacher needs, and the population served. For this reason, feedback from administrators may need to be tailored accordingly. Implications are discussed and may be useful for administrators to conduct teacher evaluations with a set of concrete solutions for teachers in specific areas.